The Influence of Simple Respiratory System Media on Students’ Learning Outcomes in Class V Science and Science Subjects at SD GMIT Airnona 1 Kupang - Batmaro, Mardini Y.L; Tanggur, Femberianus S.; Nahak, Kristina E. Noya (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The aim of the research was to determine the effect of simple respiratory system media on student learning outcomes at SD GMIT Airnona 1 Kupang. This type of research is Quasi Experimental Design in the form of Nonequevalent Control Group Design. The population of all fifth-grade students at SD GMIT Airnona 1 Kupang is 24 students, with a sample size of 24 students and data collection techniques using observation, documentation and multiple-choice test questions. Data were analyzed using hypothesis testing and t-test. The results of the research show that the average posttest for the experimental class and control class using the t-test was 82.08>53.75 with a difference of 7.525. Furthermore, through hypothesis testing (paired samples test), it shows that the sig (2-tailed) t-test for equality of means is 0.000 < 0.05, meaning that Ho is rejected and Ha is accepted. So it can be concluded that there is a significant influence of the influence of simple respiratory system media on learning outcomes in science and science subjects in class V of SD GMIT Airnona 1 Kupang.